Feto-Maternal Outcome after Trial of Vaginal Delivery in Women Having the History of Previous Caesarean Section: A Cross-Sectional Study in Pakistan - Sadia Kakar, Fouzia Jan, Zeb Un Nisa Jogezai, Saira Ali, Nazish Baloch, Rozina Khan (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the fetus and maternal outcome on the trial of vaginal delivery after a previous single Caesarean Section (CS). Study design: A cross-sectional study Place and Duration: This study was conducted at Bolan Medical Complex Hospital Quetta from January 2021 to December 2021 Methodology: A total of 108 cases were incorporated in the study who had a previous single CS. Patients’ vital signs, fetal cardiac activity, pain and tenderness of the lower abdomen, and fetal distress were observed extensively during the labor. Data was collected with pre-designed Performa, and written informed consent was obtained on a consent form. The hospital committee was given authorization, and the data was analyzed for outcomes. Results: A total of71 patients (65.7%) had a successful vaginal delivery, while 37 (34.3%) required a repeat emergency cesarean section. Out of 71 vaginal deliveries, 47 (66.2%) were between the ages of 19 and 30 years, while 24 (33.8%) were between 31 and 45 years. Out of 37 instances, 22 (59.5 %) were between the ages of 19 and 30 years, while 15 (40.5 %) were between 31 and 45 years. The distribution of cases according to fetal distress in emergency cesarean section patients showed that 8 cases (21.6%) experienced fetal distress, and 29 (78.4%) did not develop any fetal complication. Conclusion: This study demonstrates the higher frequency of fetal distress in CS than vaginal delivery. Pregnant patients should be encouraged to have vaginal deliveries to reduce future morbidity related to CS.